Enhanced efficiency of planar perovskite solar cells via a two-step deposition using DMF as an additive to optimize the crystal growth behavior. Issue 25 (8th June 2017) - Mo, Jiajie; Zhang, Chunfu; Chang, Jingjing; Yang, Haifeng; Xi, He; Chen, Dazheng; Lin, Zhenhua; Lu, Gang; Zhang, Jincheng; Hao, Yue
Abstract : We present a facile way towards the use of the polar solvent additive in the inter-diffusion two-step sequential deposition method for a high quality perovskite film. Abstract : The performance of perovskite solar cells (PSCs) is extremely dependent on the morphology and crystallization of the perovskite film. However, the complete conversion of PbI2 to perovskite and controlling the perovskite crystal size as well as its surface morphology are challenging in the conventional two-step sequential deposition method. We herein present a facile method involving the use of a polar solvent additive in an inter-diffusion two-step sequential deposition method to achieve a high-quality perovskite film. The results showed that the addition of a small amount of DMF solvent into the MAI precursor solution could help the complete conversion of PbI2 to perovskite, and at the same time could also reduce the pinholes, improve the film morphology, increase the grain sizes and enhance the film absorption ability. The improved perovskite film quality results in the boosting performance of PSCs. Consequently, an optimized device with power conversion efficiency as high as 19.2% is obtained. This current method provides a highly repeatable route for enhancing the PSC performance with the inter-diffusion sequential solution deposition method.